Significant contributing causes of cancer deaths among Hispanics in Colorado, USA, 1983-1992 Causas que contribuem para óbitos por câncer em latinos no Colorado, EUA, 1983-92 - Kimberley Sweitzer; Lorann Stallones (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
Cancer deaths in the state of Colorado, U.S.A., totaled 53,921 between 1983 and 1992. Death certificates for this period were used to evaluate Hispanic cancer deaths by contributing causes of death and primary occupation of the decedent. The relative risks for diabetes and liver disease as contributing causes of death were significantly higher among Hispanics when compared to non-Hispanics who had also died of cancer (RR for diabetes = 1.90; 95% C.I. (1.64,2.19) and RR for liver disease = 1.44; 95% C.I. (1.23,1.68)). Hispanics who had died of cancer were significantly less likely to have drug abuse as a contributing cause of death when compared to non-Hispanics (RR for drug abuse = 0.69; 95% C.I. (0.52,0.91)). Laborers, service workers, and clerical workers who were Hispanic, were significantly more likely to die of cancer with either diabetes or liver disease as a contributing cause of death than were non-Hispanics in the same occupational category (p<0.05). Chronic diseases, such as diabetes and liver disease, may be reducing the survivability of cancer among Hispanics. Entre 1983 e 1997, ocorreram 53.921 óbitos por câncer no Estado do Colorado, EUA. Os atestados de óbito para este período foram utilizados para avaliar as causas que contribuíram para a morte e a ocupação principal dos óbitos por câncer ocorridos em latinos neste período. Os riscos relativos para diabetes e doença hepática como causas associadas ao óbito foram significativamente maiores em latinos, comparativamente com não latinos que também faleceram com câncer (diabetes RR = 1,90; I.C. 95% 1,64-2,19; doença hepática RR = 1,44; I.C. 95% 1,23-1,68). O consumo de drogas como causa associada à morte entre latinos que faleceram por câncer aparentou ser significativamente menor que em não latinos (RR = 0,69; I.C. 95% 0,52-0,91). Operários, servidores públicos e trabalhadores de escritório de origem latina tenderam a apresentar diabetes e doença hepática como causas associadas à morte por câncer em maior freqüência, estatisticamente significativa, que não latinos nos mesmos ramos de atividade (p<0,05). Doenças crônicas, como diabetes e doença hepática, podem estar reduzindo a sobrevida por câncer em latinos.